2015
DOI: 10.1080/14786419.2015.1046070
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and biological evaluation of the volatile constituents from the aerial parts of Nephrolepis exaltata (L.) and Nephrolepis cordifolia (L.) C. Presl grown in Egypt

Abstract: The essential oil from the aerial parts of Nephrolepis exaltata and Nephrolepis cordifolia obtained by hydro-distillation were analyzed by gas chromatography/ mass spectrometry. The essential oils exhibited potential antibacterial and antifungal activities against a majority of the selected microorganisms. NEA oil showed promising cytotoxicity in breast, colon and lung carcinoma cells. The results presented indicate that NEA oil could be useful alternative for the treatment of dermatophytosis. Comparative inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Lower water addition (1:1) discharged (Z)‐2‐octen‐1‐ol and formed 2‐methoxy‐4‐vinylphenol, which are responsible for a vinegar smell and flavouring agent compounds, respectively (Jeong et al ., 2011; Le et al ., 2012), while higher water addition (1:2) discharged 1‐tetradecanol, 1‐hexadecanol, and 4,4,6‐trimethyl‐cyclohex‐2‐en‐1‐ol and induced the formation of 2,4‐hexadien‐1‐ol, 2‐hexyn‐1‐ol, and 3,5‐octadien‐2‐ol. The eliminated compounds are responsible for a fatty odour while the formed compounds are responsible for fruity and herbal perception (Noweck & Grafahrend, 2006; Feng et al ., 2015; Wang et al ., 2015; El‐Tantawy et al ., 2016; Polat et al ., 2018; Ju et al ., 2021). The results revealed that AH potentially removed the essential oil odour perception and dominantly formed pleasant smells including a grainy and desired flavour.…”
Section: Resultsmentioning
confidence: 99%
“…Lower water addition (1:1) discharged (Z)‐2‐octen‐1‐ol and formed 2‐methoxy‐4‐vinylphenol, which are responsible for a vinegar smell and flavouring agent compounds, respectively (Jeong et al ., 2011; Le et al ., 2012), while higher water addition (1:2) discharged 1‐tetradecanol, 1‐hexadecanol, and 4,4,6‐trimethyl‐cyclohex‐2‐en‐1‐ol and induced the formation of 2,4‐hexadien‐1‐ol, 2‐hexyn‐1‐ol, and 3,5‐octadien‐2‐ol. The eliminated compounds are responsible for a fatty odour while the formed compounds are responsible for fruity and herbal perception (Noweck & Grafahrend, 2006; Feng et al ., 2015; Wang et al ., 2015; El‐Tantawy et al ., 2016; Polat et al ., 2018; Ju et al ., 2021). The results revealed that AH potentially removed the essential oil odour perception and dominantly formed pleasant smells including a grainy and desired flavour.…”
Section: Resultsmentioning
confidence: 99%
“…Tannins (11.5 mg/100 g), alkaloids (9.1 mg/100 g), flavonoids (16.5 mg/100 g), phenols (8.3 mg/100 g), saponin (1.2 mg/100 g) and glycosides (5.4 mg/100 g) are estimated in the leaflets [ 227 ]. Essential oil obtained from the aerial parts constitutes nonanal (10.6%), β-ionone (8%), eugenol (7.2%) and anethol (4.6%) [ 228 ]. Sequoyitol, β-sitosterol, fern-9(11)-ene, oleanolic acid, myristic acid octadecylester, hentriacontanoic acid and triacontanol are isolated from the plant material [ 229 ].…”
Section: Distribution Ethnomedicine Pharmacognosy and Phytochemistry ...mentioning
confidence: 99%
“…The fern has been studied for its soil phytoremediation properties (Sultana et al, 2015). The effects of its volatile oil (El-Tantawy et al, 2016) and its possible hormonal and cytotoxic effects on human cancer cells (Raimi et al, 2020) has also been documented. The species is in ethnomedicine in the island of Fiji to treat women's menstrual disorders (Popovici et al, 2018).…”
Section: Introductionmentioning
confidence: 99%